Using multi-layer nested network to optimise spatial structure of tourism development between urban and rural areas based on population mobility. Issue 4 (April 2022) - Liu, Zhao; Wang, Fang; Xue, Pengcheng; Xue, Feng
Under the bidirectional flow pattern of urban and rural factors, the tourism industry has become an important way to promote the vitality of urban and rural areas because of rural gentrification and city migration. By constructing a 'node-link-setting' networked land use model, this paper maps the tourism flow and geographic space networks, proposes a multi-layer nested network theory with spatial relevance from the mobility perspective to solve practical problems, such as urban–rural dual opposition and functional segmentation. We studied the high-precision mobile smart phone signalling data combined geographical data of Yichang, analysed the dynamic change process and comprehensive development mode characteristics of tourism attractions in 92 villages and towns through the social network analysis, compared tourism flow network changes in Yichang over time to construct a tourism flow network of Yichang, analysed the level and location of tourism nodes in the network and classified the tourist destinations to reveal the spatial-temporal evolution process and change the rule of the tourism flow network. The differences were compared by constructing traffic geography and infrastructure networks. The purpose is to propose guidance countermeasures for regional village unit tourism facility construction and industrial development and to maintain the integrity of spatial correlation and structural optimisation.